Optimizing of Temperature and Pressure in a Modified Plug Flow Reactor to Enhance Benzene Conversion with Process Simulation Software - Ardi Wiranata Hutabarat; Arnanda R.H. Sitio; Ar Rahma Intan Zahkia; Azhari Eliana Damanik; Muhammad Danil Huda; Padilah Ulpah Pulungan (Journal of Chemical Engineering Research Progress, 2026)
The increase in industrial dependence on benzene demands a more efficient, high-conversion hydrodealkylation (HDA) process. The HDA of toluene is highly sensitive to temperature and pressure, and inaccuracies in operating conditions can cause side reactions and accelerate catalyst deactivation. This study determined optimal temperature–pressure conditions in a plug flow reactor through steady-state Aspen HYSYS simulation using the Peng–Robinson model and parameter interaction analysis in Design Expert. The results showed a synergistic effect, with temperature as the dominant factor and pressure enhancing conversion. Optimal conditions of 710.8 °C and 67.6 atm produced 90.39% conversion, while the lowest conditions resulted in < 5%. These findings confirm that precise control of operating parameters improves reactor performance and hydrogen utilization, supporting a more stable and energy-efficient HDA process. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).